HISTORY OF RELIGIOUS EXTREMISM IN THE MIDDLE EAST (Religious dialogue and cooperation, 2022)
The origin of World War II was “Nazism”, a violent totalitarian ideologythatcrossed national borders and took the lives of more than 55 million aroundtheworld.History very often claimed that ethnically motivated religious violence evenbetweencommunities practicing the same religion is very usual. The terrorist attack on USA from 11.09.2001 represents a cornstone for expansionofreligious extremism which easly developed in different forms of terrorism. Religious extremism offers various challenges at the national, regional and global levelsand requires policy makers and practitioners to appreciate the unique natureof theseideologies, many of them seeking the wholesale destruction of civic order as opposedtoits reform or even restructuring. Conflicts incited by religious extremismare forcingthedisplacement of millions people around the world. Middle East as a region is most vurnelable to religious extremismesspecialyamongyoungsters. Esspecially after 11/09 UN, NATO, EU and other regional andworldorganization for collective security and defense were focused on developing modernandcomman measures for coping with religious extremism. The main research focus of this paper is to give an historical retrospective on developmentof religious extremism and to gave an comman interoperative and efective measuresofUN, NATO and EU for delling with religious extremism. Also the main researchingtargetsof this paper is religious extremism among young people in the Middle East.
Keywords: historical retrospective; religious extremism; Middle East; recruitment; countermeasures